Implementasi Komunikasi Interpersonal antara Tutor dan Siswa pada Kegiatan Speaking Class di Kind English Course - Daniel, Angelia Eunike; Anggraeni, Ni Wayan Yuli (Pusat Riset dan Inovasi Nasional, 2026)
This study explores the implementation of interpersonal communication between tutors and students in speaking class activities at the Kind English Course by applying DeVito’s Interpersonal Communication Theory. Interpersonal communication plays a vital role in English language learning, especially in speaking classes where real-time interaction directly shapes students’ engagement and learning outcomes. Using a qualitative literature review method, this research examines how the five key components of interpersonal communication—openness, empathy, supportiveness, positiveness, and equality—are applied within instructional practices. The analysis reveals that tutors who demonstrate openness and empathy foster stronger emotional connections with students, which encourages them to speak more confidently. Supportive and positive communication behaviors further create a safe and motivating learning environment where students feel valued and understood. Additionally, the principle of equality helps reduce hierarchical barriers, enabling more collaborative and interactive learning dynamics. Overall, the findings indicate that the consistent application of interpersonal communication principles significantly enhances students’ participation, confidence, and speaking proficiency. This study contributes to a deeper understanding of how communication quality influences language learning and underscores the importance of interpersonal competence among tutors in developing effective and engaging speaking class experiences.